Subjectivity, Rationality, and the Tragedy of culture: Georg Simmel at the court of Max Horkheimer - Ruggieri, Davide (Simmel Studies)

(untitled) (Edizioni ETS, 2025)
This paper explores some common theoretical points between the sociologist Georg Simmel (1858-1918) and Max Horkheimer (1895-1973), the director of the Institut für Sozialforschung, “spiritus rector” and a key figure of the early Frankfurt School. In addition to some biographical connections linking Horkheimer to Simmel, they share particular views about the profound transformations in social and cultural life brought about by modernity. Both Simmel and Horkheimer focus on socialization processes resulting from rationalization, as well as the increasing individualization that characterize the stage of social agency. They both believe that modern life is defined by new forms of rational organization, largely influenced by the “metropolization” of social and cultural life. Horkheimer refers to this as “instrumental reason,” while Simmel describes it as the “intellectualization of life.” Moreover, they emphasize the concept of the “objectification of culture” - the growing necessity for individuals to engage with and incorporate the “objective” products of culture in order to affirm their identities (this is compounded by what Simmel calls the “externalization of life”). These last aspects for both authors may lead to new forms of social pathologies and alienation. Ultimately, this paper demonstrates Horkheimer’s reliance on Simmel’s social philosophy as he seeks to formalize his Critical Theory program.